Agronomic performance of arugula (Eruca sativa L.) in different soil cover managements (Research, Society and Development, 2021)
This research focuses on assessing the agronomic performances of the arugula under different types soil cover managements. The experiment was conducted in Florianopolis-SC, using Randomized Complete Block Design, with four treatments and four repetitions. The variety Rococo was sowed directly with a spacing of 5 x 15 cm between each plant and lines, respectively. The different experimental conditions were no weeding (control), dead mulch, plastic sheet and with weeding. The number of leaves, the foliar area and the fresh matter were measured. The experiment was conducted for 33 days after the seeding. The statistical processing of the results was conducted through the analysis of variance and the Tukey’s test to differentiate the means at probability of 5%. The manual weeding of spontaneous plants was significantly superior to no weeding for the leaf area, fresh weight and productivity. There were no differences between treatments for the number of leaves. The results showed a better performance of the arugula when managed with manual weeding, but the management with dead mulch or plastic canvas showed similar performance, being viable alternatives.